Proposing an Arabic letters Coding system for different Programming languages (Al-Mansour Journal, 2022)
Abstract This paper deals with the problem of using Arabic tex ts by researchers even in programming languages or internet search. The difficulties of Arabic language in programming languages and search the Internet have created a need to propose a system to code Arabic alphabets in all its forms and to be used in various applications and languages software that do not support the Arabic language in their content. Thus, it is possible to deal with the Arabic language and conducts many operations easily to download them through this system by using any Arabic text. The proposed system depends on three algorithms: the first is to code Arabic letters in any text, the second (code-function) is to code letters in any position shape in the text (first letters, middle letters, final letters and separated letters) and the third algorithm is to experiment the success rate of the proposed coding system. The proposed coding system has been examined for different texts representing Arabic poetries. Visual Basic.net 2015 language has been used to apply the proposed system. A confirmation function has been proposed which achieves 100% success rate of the coding system
Keywords: Coding alphabet letters; Letters shapes; Arabic text